A new fragment contribution‐corresponding states method for physicochemical properties prediction of ionic liquids. Issue 4 (18th October 2012) - Huang, Ying; Dong, Haifeng; Zhang, Xiangping; Li, Chunshan; Zhang, Suojiang
Abstract : A new fragment contribution‐corresponding states (FC—CS) method based on the group contribution method and the corresponding states principle is developed to predict critical properties of ionic liquids (ILs). There are 46 fragments specially classified for ILs considering the ionic features of ILs, and the corresponding fragment increments are determined using the experimental density data. The accuracy of the developed method is verified indirectly via predicting density and surface tension of ILs. The results show that the FC—CS method is reasonable with an average absolute relative deviation less than 4%. With the calculated critical properties, corresponding states heat capacity (CSHC) and corresponding states thermal conductivity (CSTC) correlations are proposed to predict heat capacity and thermal conductivity of ILs, respectively. The predicted results agreed well with the experimental data. The proposed FC—CS method and the two corresponding states correlations are important for design, simulation, and analysis of new ionic liquid processes. © 2012 American Institute of Chemical Engineers AIChE J, 59: 1348–1359, 2013